Pressure‐Driven Eu2+‐Doped BaLi2Al2Si2N6: A New Color Tunable Narrow‐Band Emission Phosphor for Spectroscopy and Pressure Sensor Applications - Wang, Yichao; Seto, Takatoshi; Ishigaki, Kento; Uwatoko, Yoshiya; Xiao, Guanjun; Zou, Bo; Li, Guangshe; Tang, Zuobin; Li, Zebin; Wang, Yuhua (Advanced Functional Materials, 2020)
A series of BaLi2Al2Si2N6 (BLASN): xEu2+ phosphors are successfully synthesized and their crystal structure and luminescence properties under varying hydrostatic pressures are reported herein. Structure variation is analyzed using in situ high‐pressure X‐ray diffraction and Rietveld refinements. Based on decay curves and Gaussian fitting of emission spectra, the presence of two photoluminescence centers is demonstrated. BaLi2Al2Si2N6: 0.01Eu2+ exhibits an evident peak position shift from 532 to 567 nm with an increase in pressure to ≈20 GPa. The possible factors and mechanisms for the variations are studied in detail. At a pressure of 16 GPa, BLASN: Eu2+ realizes a narrow yellow emission with a full width at half maximum of ≈70 nm. The addition of BLASN: Eu2+ (16 GPa) to the commercial white light‐emitting diodes combination consisting of an InGaN chip, β‐SiAlON: Eu2+, and red K2SiF6:Mn4+, can increase the color gamut by ≈15%, demonstrating the promising potential of pressure‐driven BLASN: Eu2+ for wide‐color gamut spectroscopy applications. Moreover, the emission shifts arising from pressure variation and the distinct color changes enable its potential utility as an optical pressure sensor; the material exhibits high pressure sensitivity (dλ/dP ≈ 1.58 nm GPa−1) with the advantage of visualization. A new color tunable narrow‐band emission phosphor with high color purity is developed by controlling the external hydrostatic pressure. An obvious peak shift and color variation from green to yellow is successfully realized. The excellent color tunability and high pressure sensitivity give the material certain advantages in the fields of spectroscopy application and pressure sensors.